Evaluasi Penerapan Tentang Bahaya Limbah di lingkungan Masyarakat di Pabrik Kelapa Sawit PKS PTPN-II Sawit Seberang - Monijiso Fatemaluo (JEMA: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study evaluates the implementation of waste hazard management in the community environment around the PTPN-II Sawit Seberang Palm Oil Mill (PKS). The objectives of the study are (1) to assess the compliance of liquid, solid, and hazardous waste management with applicable regulations, (2) to map potential health-environmental risks for the community, and (3) to formulate operational improvement recommendations. The method used is a mixed approach: field observation and document audit (SOP, manifest records, IPAL logs), directed interviews with management, workers, and residents, and measurement of key environmental quality parameters (indicative for liquid waste: pH, BOD, COD, TSS, oil & grease; for air: odor and particles around the pond area; and review of hazardous waste segregation-labeling practices). The analysis was conducted through compliance assessment, risk matrix (likelihood-consequence), and triangulation of qualitative-quantitative findings. The evaluation results indicate that liquid waste processing practices have been running with a moderate level of compliance, but gaps are still found in controlling TSS and odor during peak load periods; B3 waste management needs strengthening in terms of segregation, labeling, and storage duration; and potential community exposure arises from odor emissions and runoff during heavy rains. The risk assessment places most scenarios in the medium category, with several specific scenarios (local oil/grease spills) in the medium-high category without mitigation. Key recommendations include optimizing WWTP operations (equalization and sludge handling), a 3R solid residue program, traceability of B3 manifests, improving SOPs and training, strengthening emergency preparedness, and establishing an evidence-based public complaint mechanism. These findings are expected to form the basis for measurable, continuous improvement for the company and the protection of the environmental health of the surrounding community.